2002
DOI: 10.1094/cchem.2002.79.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Additive Effects of Three High Molecular Weight Glutenin Subunit Loci. II. Effects on Wheat Dough Functionality and End‐Use Quality

Abstract: Cereal Chem. 79(2):301-307Understanding the relationship between basic and applied rheological parameters and the contribution of wheat flour protein content and composition in defining these parameters requires information on the roles of individual flour protein components. The high molecular weight glutenin subunit (HMW-GS) proteins are major contributors to dough strength and stability. This study focused on eight homozygous wheat lines derived from the bread wheat cvs. Olympic and Gabo with systematic del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 11 publications
4
28
0
Order By: Relevance
“…Gupta et al (1993) noted that not only the quantity of the glutenin network but also its size was important. Beasley et al (2002) concluded that variations in mixing time could be best explained by variations in acid-extractable polymeric protein.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al (1993) noted that not only the quantity of the glutenin network but also its size was important. Beasley et al (2002) concluded that variations in mixing time could be best explained by variations in acid-extractable polymeric protein.…”
Section: Resultsmentioning
confidence: 99%
“…3 To define wheat quality, both the qualitative and quantitative aspects of wheat proteins have to be addressed. Wheat protein quality depends on the presence or absence of specific high-molecular-weight glutenin subunits (HMW-GS), 4 low-molecular-weight glutenin subunits (LMW-GS) 5 and gliadins. 6,7 It also depends on the ratio of monomeric to polymeric proteins 8,9 and the molecular size distribution of glutenin.…”
Section: Introductionmentioning
confidence: 99%
“…However, this relationship was insufficient to explain the inherent qualities of wheat flours of different grades (Suchy et al, 2003). Subsequently, many researchers established relationships between flour quality and gliadins (Hoseney et al, 1969a;Preston and Tipples, 1980;Békés et al, 1992;Khatkar et al, 2002), glutenins (Gupta et al, 1995;Beasley et al, 2002) and the ratio of gliadins to glutenins (Gupta et al, 1992).…”
Section: Introductionmentioning
confidence: 99%